Selection of upland rice cultivars for saline-sodic soils. I. Tests of germination and growth - Gheyi, Hans Raj; Barros, Adilson David de (Pesquisa Agropecuaria Brasileira, 2014)
Greenhouse experiment under ambient conditions was carried out with the objective to select cultivars of irrigated rice (Oryza sativa L.) tolerant to saline-sodic medium. As a substrate, a loam soil from Irrigated Perimeter of São Gonçalo-Setor 10 having 86.5% exchangeable sodium percentage was employed. The cultivars under study showed significant differences at 0.01 level of probability for percentage of germination as well as for the height of seedlings after 14 and 31 days of planting. However, for 21 days the results were found to be significant only at 0.05 level. Though all cultivars studied showed good percentage of germination, cultivars IR 4573-4-3-7-14, IR 9698-48-3-3-2 and IR 8 were found to be the best. Adopting the criterion of height of seedlings after 31 days of planting, the cultivars IR 4619-48-3-3-6-1, IR 9729-1 06-1-2-2, IR 15500-32-1-3-2 and IR 4595-4-1-13 may be considered as relatively more tolerant, while IR 9129-192-2-4-3, IR 13385-48-1 and IR 11933-299-2-3-1 were found to be susceptible. The study shows the possibility of planting rice crop in saline-sodic soils at present abandoned without any treatment or incorporation of chemical amendment.